An Analysis of Clostridium difficile Environmental Contamination During and After Treatment for C difficile Infection. (17th August 2020) - Davies, Kerrie; Mawer, Damian; Walker, A Sarah; Berry, Claire; Planche, Timothy; Stanley, Phil; Goldenberg, Simon; Sandoe, Jonathan; Wilcox, Mark H
Abstract: Background: Lower Clostridium difficile spore counts in feces from C difficile infection (CDI) patients treated with fidaxomicin versus vancomycin have been observed. We aimed to determine whether environmental contamination is lower in patients treated with fidaxomicin compared with those treated with vancomycin/metronidazole. Methods: The CDI cases were recruited at 4 UK hospitals (Leeds, Bradford, and London [2 centers]). Environmental samples (5 room sites) were taken pretreatment and at 2–3, 4–5, 6–8, and 9–12 days of treatment, end of treatment (EOT), and post-EOT. Fecal samples were collected at diagnosis and as often as produced thereafter. Swabs/feces were cultured for C difficile ; percentage of C difficile -positive samples and C difficile bioburden were compared between different treatment arms at each time point. Results: Pre-EOT (n = 244), there was a significant reduction in environmental contamination (≥1 site positive) around fidaxomicin versus vancomycin/metronidazole recipients at days 4–5 (30% vs 50% recipients, P = .04) and at days 9–12 (22% vs 49%, P = .005). This trend was consistently seen at all other timepoints, but it was not statistically significant. No differences were seen between treatment groups post-EOT (n = 76). Fidaxomicin-associated fecal positivity rates and colony counts were consistently lower than those for vancomycin/metronidazole from days 4 to 5 of treatment (including post-EOT); however, the only significant difference was in positivity rate at days 9–12 (15% vs 55%, P = .03). Conclusions: There were significant reductions in C difficile recovery from both feces and the environment around fidaxomicin versus vancomycin/metronidazole recipients. Therefore, fidaxomicin treatment may lower the C difficile transmission risk by reducing excretion and environmental contamination. Abstract : Environmental contamination of the area around patients with Clostridium difficile infection treated with fidaxomicin may be reduced compared with those treated with vancomycin/metronidazole. This may be related to a reduced bioburden in the feces of fidaxomicin-treated patients.